A Proposed Theoretical Model to Improve Public Participation Towards Renewable Energy (RE) Development in Malaysia - Abdullah, WMZW; Zainudin, WNRA; Ishak, WWM (Amer Scientific Publishers, 2024)
Indexed by WOS